Pengaruh Pelatihan Makhorijul Huruf dan Tajwid Terhadap Peningkatan Pembacaan Al-Quran Santri Musholla Mambaul Hikam Desa Jurang Jero - Sintawati, Dewi; Yusrina Maharani , Desyka (Najah: Journal of Research and Community Service, 2026)
The reverent training of letters and tajwid for santri mushola mambaul hikam in the village of jero cliff aim to improve the quality of Koran reading for the sons and daughters of mushola mambaul hikam. The methods used in this study apply the methods of speech, discussion and practice to read the qur 'an well and correctly according to science. To see how successful the activity is in achieving the desired goals, post - and preexercise tests are carried out. After 16 days of training, there was a significant improvement, as indicated by tests performed before and after training.